FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA PENGGUNAAN METODE KONTRASEPSI VASEKTOMI DI DESA BANJARMULYA KECAMATAN PEMALANG KABUPATEN PEMALANG TAHUN 2010 - Indah Siloka Dina kebidanan (Siklus : Journal Research Midwifery Politeknik Tegal, 2012)
Factors affecting the use of contraceptive methods Vasectomy in Banjarmulya Village Pemalang District Pemalang Regency Year 2010. New paradigm of the national family planning program has changed its vision of realizing a vision to realize NKKBS "Quality family 2015". Vasectomy is a cut or blockage of a channel that is called the vas deferens that deliver sperm from the testicles to the penis to prevent sperm phat (glasier,2006). According to gatra (2004) factors affecting the use of male contraceptive methods can be viewed from various aspect of them are from the man himself (knowledge, education, the reqirements of men), environmental factors, social, cultural, income, religion, wife or family, jobs, lack of information, KB abused by men for sexual perversions of the health service. Formulation of the problem in this research is "what are the factors affecting low use of contraceptive methods, vaectomy in banjarmulya village pemalang district pemalang regency year 2010?". This study aimed to describe the factors affecting low use of contraceptive methods, human experience with snow ball sampling of vasectomy acceptors in the banjarmulya village pemalang district pemalang regency. District by way of depth interview with the main instrument is the researcher himself while supporting instrument using interview guides. The result obtained repondents perception about the vasectomy is less good enough, because the majority of respondents not knowing the definition vasectomy, vasectomy benefits, drawbacks and advantages. most respondents said that vasectomy is not castration. According to respondents KB vasectomy viewed from the standpoint of religion is not forbidden by the religion and the respondents do not feel guilty after vasectomy. Key words :     Vasectomy, Perception, Social Culture, Religion And Belief